2014
DOI: 10.1007/s00402-014-2111-8
|View full text |Cite
|
Sign up to set email alerts
|

Distal femoral fractures in the elderly: biomechanical analysis of a polyaxial angle-stable locking plate versus a retrograde intramedullary nail in a human cadaveric bone model

Abstract: Based on our results, no statements regarding the superiority of either of the devices can be made. Even though the load to failure values for both osteosyntheses were much higher than the loads experienced during normal walking; however, because only axial loading was applied, it remains unclear whether both osteosyntheses meet the estimated requirements for postoperative full weight-bearing for an average heavy patient with a distal femoral fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 43 publications
1
14
0
2
Order By: Relevance
“…Moreover, the smooth placement of the intramedullary nail will be affected if there is bone end hardening or stenosis of the medullary cavity. 19,20 In recent years, the use of locking plates combined with external fixators for bone transport has achieved good results. [21][22][23] Compared with intramedullary nails, locking steel plates can allow for screwing in the transported segment, increasing its stability, and eliminating the time required to heal the anchor point.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the smooth placement of the intramedullary nail will be affected if there is bone end hardening or stenosis of the medullary cavity. 19,20 In recent years, the use of locking plates combined with external fixators for bone transport has achieved good results. [21][22][23] Compared with intramedullary nails, locking steel plates can allow for screwing in the transported segment, increasing its stability, and eliminating the time required to heal the anchor point.…”
Section: Discussionmentioning
confidence: 99%
“…The femora were enveloped in humidified clothes using a liquid, consisting of 96% ethanol and < 2% formaldehyde. To prevent dehydration of the specimens, they were stored in a cold storage room [7].…”
Section: Specimensmentioning
confidence: 99%
“…19 However, although no plate was present laterally, it was still found that the main complication with retrograde nailing was the prominence of distal locking screws. 22,37 Finally, it was shown by Demirtas et al 37 that the complications, union rate, and functional results of modern intramedullary nailing are no different than that of modern plating technology for extraarticular distal femoral fractures. A recent study on the fixation of distal femoral fractures with retrograde intramedullary nailing has demonstrated that modern locked plating and nailing present no significant difference in loadto-failure and that nails undergo less plastic deformation than plates.…”
Section: Intramedullary Nailingmentioning
confidence: 99%
“…19 Intramedullary nailing does have improved axial stability to plates and did lead to good results with a quoted 2.8% nonunion rate. 22 It also has been shown that intramedullary nailing is not as good as plates at controlling fractures with significant comminution, and they can lead to an incidence of malrotation as high as 28% and can have a nonunion rate of up to 15%. 25,35,36 Another common concern with retrograde intramedullary nails is knee sepsis from the arthrotomy created; however, review of the literature did not demonstrate this to be a problem.…”
Section: Intramedullary Nailingmentioning
confidence: 99%